2018
DOI: 10.1194/jlr.d084525
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping in zebrafish reveals genetic and diet-induced adiposity changes that may inform disease risk

Abstract: The regional distribution of adipose tissues is implicated in a wide range of diseases. For example, proportional increases in visceral adipose tissue increase the risk for insulin resistance, diabetes, and CVD. Zebrafish offer a tractable model system by which to obtain unbiased and quantitative phenotypic information on regional adiposity, and deep phenotyping can explore complex disease-related adiposity traits. To facilitate deep phenotyping of zebrafish adiposity traits, we used pairwise correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…From 456 zebrafish, 67 traits were quantified in each fish, including AT area measurements, measures of body size (SL and body area), composite AT groupings (total AT, VAT and SAT) and AT proportionality assessments (VAT:SAT ratios). Correlations were computed between each trait and assessed to determine how adiposity relationships and patterns change in fish of distinct stages [53]. As expected, considerable differences in adiposity profiles at distinct stages were observed.…”
Section: Deep Phenotyping and Phenomics To Study Complex Quantitativmentioning
confidence: 78%
See 4 more Smart Citations
“…From 456 zebrafish, 67 traits were quantified in each fish, including AT area measurements, measures of body size (SL and body area), composite AT groupings (total AT, VAT and SAT) and AT proportionality assessments (VAT:SAT ratios). Correlations were computed between each trait and assessed to determine how adiposity relationships and patterns change in fish of distinct stages [53]. As expected, considerable differences in adiposity profiles at distinct stages were observed.…”
Section: Deep Phenotyping and Phenomics To Study Complex Quantitativmentioning
confidence: 78%
“…We found that FLD+ area was an accurate predictor for TAG mass for each AT (R 2 = 0.78, 0.87 and 0.82; all P < 0.0001), which supported the method of area measurements of individual ATs as an accurate estimator of lipid content. These methods are relatively fast to undertake and large sample sizes were achievable [51,53]. Therefore, FLDs allow the large-scale collection of quantitative adiposity data.…”
Section: The Regional Distribution Of Adipose Tissues Is a Strong Prementioning
confidence: 99%
See 3 more Smart Citations